Strategic management accounting information elements: Malaysian evidence / Raman Noordin, Yuserrie Zainuddin and Michael Tayles - Zainuddin, Yuserrie; Tayles, Michael (Accounting Research Institute, Faculty of Accountancy & UiTM Press, 2009)
Motivated by the paucity of published empirical evidence on SMA this paper reports the results of an exploratory study carried out on Electrical and Electronics (E&E) companies operating in Malaysia. Specifically, it explores the extent of strategic management accounting (SMA) information elements usage among Malaysia’s E&E companies. The results indicate that E&E companies use SMA information elements extensively. The results imply that companies are extending their management accounting information towards more externally focused and strategic material. This finding enriches our current knowledge about the extent of SMA information usage among organisations. It also supports the findings of several previous researches which suggested that companies operating in today’s environment emphasise beyond traditional management accounting information.